IMPLEMENTASI KEBIJAKAN PEMBUATAN IDENTITAS KEPENDUDUKAN DIGITAL DI KABUPATEN JAYAPURA - Nursidah, Sarah; Ohoiwutun, Yosephina; Aedah, Nur (Universitas Cenderawasih, 2024)
This research aims to explain how the implementation of the Digital Population Identity (IKD) Policy in Increasing Public Awareness of Population Document Ownership in Jayapura Regency which also reveals the inhibiting and supporting factors of the policy implementation, as well as analyzing efforts to optimize its implementation. This research is important, because Digital Population Identity (ID) is a strategic innovation to improve the efficiency of public services, but its implementation in Jayapura Regency still faces challenges that require implementative solutions. This research uses a type of qualitative research with a public policy research approach. Data collection techniques include interviews, observation, and documentation. The research instruments used were interview guides, notebooks, and recording devices. The informants were selected purposively, while the data analysis followed the stages of data reduction, data presentation, and conclusion drawing and verification. The results showed that the implementation of the Digital Population Identity (IKD) policy in Jayapura Regency faced challenges in the aspects of communication, resources, disposition, and bureaucratic structure. Socialization through various media has been carried out, but limited human resources, infrastructure, and budget are the main obstacles. Nevertheless, the commitment and proactive attitude of policy implementers show the important role of disposition in the success of the program. To be more effective, an increase in resource allocation, additional human resources, training, and SOP adjustments are needed. An integrated socialization strategy and revision of the Dukcapil Renstra to include IKD as a priority are also important to increase public awareness and achieve the IKD target.